Opportunities and Implications of Motivation Theories in an Apparel Industry - Rahman, Mustafizur; Dey, Samrat Kumar; Tahiduzzaman, Md.; Tahiduzzaman, Md.; Rahman, Md. Sumon (IJRDO - Journal of Business Management, 2017)
In developed countries, most of the apparel industries have powerful facilities in the production system. In pretending to that they use high technology, resources, raw-materials etc. For that purposes, Bangladesh has not available facilities but we have the available man power to lead a good production. A large number of the worker employed in textile or apparel industry, but they can’t be used effectively because authority can’t fulfill their job satisfaction. As a result, the productivity of our industry is not fruitful. In order to enhance productivity, top management or production manager in the apparel industry are always anxious about the way of motivating workers. Motivation is a set of processes that stimulate and create willingness of the organizational employees to do something to attain a particular goal by doing a better performance on the job. Under this study, various motivating factors are found out in apparel industry of Bangladesh and try to find out how motivation occurs. The main purpose of this paper depicts the outcomes of the implementation of the motivation theory successfully over the workers level (about 50 workers) in a leading apparel in Bangladesh, shows a fruitful results & core benefits return from the motivated workers. The primal theme in this paper, decreasing labor costs by motivating workers to raise the level of worker productivity.